Theoretical and Methodological Foundations of Motivation as a Basis to Make Foreign Language Teaching Effective - Natalia Menshagina (Proceedings of AICS - Social Sciences, 2018)
Acknowledging that English is the world global language of science and intercultural communication, the problem of studying it is very acute today. However, not all the students are motivated enough to gain knowledge while they do not realize the importance of English. Thus the purpose of this research is to introduce the concept of “motivational maintenance” we work at. To clarify, it is the sequence of teacher's actions together with the curriculum itself aimed at creating a stable motivation for studying the language. Creating a curriculum is not enough, yet based on the